Comparative Study of Physicochemical and Microbiological Parameters of Water from Rawal Dam and its Silt Control Tank - Akber, Saima; Nazir, Aleena; Shah, Shoukat Ali; Shamima, Aktar Mst; Hadayat, Amina; Elhakim, Rabab Abd (International Journal of Scientific Research in Biological Sciences, 2022)
Water plays a vital role on this planet it is a very important factor in the living of almost every species. Water resource has been depleted, exploit, and polluted day by day due to exposure to different hazardous contaminants and misuse of water. Urbanization and increase in population increase the risk of deterioration of water quality of water resources. This study was conducted on physicochemical and microbiological analysis to determine the water quality of Rawal dam, its tributaries, and their comparison with the water quality of the silt control tank of Rawal dam which is the WASA filtration tank. The main objectives of this research water are to access the water quality parameters which are consumed by the public and to find out whether these parameters are complying with the standards given or not. Water samples were collected from the main Rawal dam, and from its tributaries that are entering the dam. All five water samples were analyzed separately to get the results and were compared with water quality standards prescribed by World Health Organization (WHO) and Pakistan Environmental Protection Agency. The samples were collected in sterilized plastic bottles during October and November 2019. Physicochemical and Biological parameters (pH, Temperature, Turbidity, ORP, EC, Salts, Total Hardness, Total alkalinity, Carbonates, Chlorides, Calcium, Magnesium, Total and Fecal coliform) were analyzed at the Chemistry Lab of Bahria University Islamabad campus. Despite, most of the parameters from upstream to the main dam exceeding the standards, most of the parameters of Dam samples and all parameters of WASA water samples were within the permissible limits given by WHO and the Pakistan Environmental Protection Agency. Microbiological analysis showed that the water samples contain high microbial counts of different pathogens like Salmonella, Shigella, and Total Coliforms in the Dam and its tributaries as compared to the WASA filtration plant (silt control tank). It is recommended to the regulatory authorities to analyze, inspect and monitor the drinking water quality regularly and it needs immediate attention of governmental bodies and public participation.